Long-term incubations provide insight into the mechanisms of anaerobic oxidation of methane in methanogenic lake sediments - H. Vigderovich; W. Eckert; M. Elul; M. Rubin-Blum; M. Elvert; O. Sivan (Biogeosciences, 2022)
Anaerobic oxidation of methane (AOM) is among the main processes limiting the release of the greenhouse gas methane from natural environments. Geochemical profiles and experiments with fresh sediments from Lake Kinneret (Israel) indicate that iron-coupled AOM (Fe-AOM) sequesters 10 %–15 % of the methane produced in the methanogenic zone (>20 cm sediment depth). The oxidation of methane in this environment was shown to be mediated by a combination of mcr-gene-bearing archaea and pmoA-gene-bearing aerobic bacterial methanotrophs. Here, we used sediment slurry incubations under controlled conditions to elucidate the electron acceptors and microorganisms that are involved in the AOM process over the long term (∼ 18 months). We monitored the process with the addition of 13C-labeled methane and two stages of incubations: (i) enrichment of the microbial population involved in AOM and (ii) slurry dilution and manipulations, including the addition of several electron acceptors (metal oxides, nitrate, nitrite and humic substances) and inhibitors (2-bromoethanesulfonate, acetylene and sodium molybdate) of methanogenesis, methanotrophy and sulfate reduction and sulfur disproportionation. Carbon isotope measurements in the dissolved inorganic carbon pool suggest the persistence of AOM, consuming 3 %–8 % of the methane produced at a rate of 2.0 ± 0.4 nmol per gram of dry sediment per day. Lipid carbon isotopes and metagenomic analyses point towards methanogens as the sole microbes performing the AOM process by reverse methanogenesis. Humic substances and iron oxides, although not sulfate, manganese, nitrate or nitrite, are the likely electron acceptors used for this AOM. Our observations support the contrast between methane oxidation mechanisms in naturally anoxic lake sediments, with potentially co-existing aerobes and anaerobes, and long-term incubations, wherein anaerobes prevail.